PENINGKATAN KUALITAS PEMBELAJARAN PKN MELALUI PENDEKATAN SOSIODRAMA PADA PESERTA DIDIK TINGKAT X SEMESTER 2 DI SMK N 4 SURAKARTA TAHUN PEMBELAJARAN 2010/2011 - Lastyawati, Sri Hastuti (MIIPS, 2010)
Research purposes are : (1) To describe civics learning process improvement withsociodrama method (2) To describe civics learning result improvement with sociodramamethod. Research location is in X class, 2nd term at SMK 4 Surakarta. This research isclass action research (PTK). Collecting data research has done by using method,observation, learning result and interview. Data analysis through three steps are: datareduction, data presentation, and conclusion/ verification. This in an active researchwith a PTK design. Research results are (1) improving student learning process quality pre cycle as 28%. Speech learning method is not giving support for student in study and learning process yet. Low student learning process quality in pre cycle because student boring of listening to the speech. Learning process quality in 1 cycle has improved as 16%, which enthusiasm student average pre cycle as 10 students (28%) in 1 cycle enthusiasmstudent average pre cycle as 16 students (44%). In sociodrama method learningprocess, student becomes more enthusiasm, because they are involved in learningprocess. Learning process quality improvement in 2 cycle as 19%. This improvementcaused by teacher managed time efficiently, praise and punishment in education andaddition mark for student can display drama well. (2) Civics learning result qualityimprovement in pre cycle includes average value as 7,4 and completeness as 16students (44%). Low value in pre cycle activity caused by low student spirit. 1 cyclelearning result improvement caused by higher spirit in study and learning process byusing sociodrama compare to speech method. 2 cycle improvement showed by averagevalue as 8,6 and completeness as 35 students (97%). It is caused by minimumcompleteness criteria (KKM) and spirit learning has been reach.